Phytotherapeutic Approaches to Kidney Stone Prevention and Detoxification: A Survey of Medicinal Plants from Manipur’s Valley Districts - Singh, Kh. Napoleon; Fatima, Tahseen; Khan, M.R.; Devi, Y. Mrinamala; Sharma, L. Dinendra (Indian Forester, 2025)
This study investigates the use of medicinal plants in the valley districts of Manipur focusing on kidney stone prevention, detoxification and urinary function. Data was collected from June 2023 to May 2024 across five districts: Imphal East, Imphal West, Bishnupur, Thoubal and Kakching. A total of 50 medicinal plant species were identified and categorized by the parts used (leaves, bark, fruits, seeds, roots) and their medicinal properties. Seeds (25%) were the most commonly used part, followed by leaves (20%) and roots (15%). The plants were from various botanical families, with Moraceae (25%), Fabaceae (15%), and Zingiberaceae (20%) being the most common. Kidney stone prevention was the primary use (40%), followed by detoxification and diuretic effects (35%). Most plants were used in doses of 3- 10 grams per day in powder or capsule form (50%) or 5-20 mL of decoction or extract (30%). The study highlights the significant role of plant-based remedies in kidney health and calls for clinical studies to validate their safety, efficacy, and standardization, emphasizing the integration of traditional knowledge into modern healthcare.